Erosion of Bedrock by Subglacial Meltwater, Soya Coast, East Antarctica - Sawagaki, Takanobu; Hirakawa, Kazuomi (Geografiska Annaler: Series A, Physical Geography)
The formation of the glacial erosional bedforms at the Soya Coast of Lützow-Holm Bay, East Antarctica is discussed. The streamlined bedforms in the studied area are classified into crescentic transverse ridges and tadpole rocks, and these bedforms are accompanied by small erosional marks (s-forms) which suport the interpretation of subglacial meltwater erosion. Some tadpole rocks are superimposed on a large roche moutonnée, and these two kinds of landform are interpreted to have different modes of formation. Observations and interpretations of these bedforms are used to reconstruct the historical development of the glacial erosional bedforms, and to draw attention to the significance and implications of subglacial meltwater erosion on the marginal area of the Antarctic Ice Sheet in the past. An initial episode of glacial plucking and abrasion produced roches moutonnées and basic large-scale landforms. Subglacial meltwater flowing peiodically into the Lützow-Holm Bay sculptured s-forms and streamlined bedforms in bedrock over much of the area. During this period, except for water-flowing phases, ice again came in contact with the bedrock to form striations superimposed on the s-forms and the hillocks.